The impact of hospital closures on geographical access: Evidence from four southeastern states of the United States - Mark L. Burkey; Joyendu Bhadury; Horst A. Eiselt; H. Toyoglu (Operations Research Perspectives, 2017)
This paper examines the effects of hospital closures on geographical access by potential patients, using data from four southeastern U.S. states. Using optimization models designed to minimize the adverse effects of hospital closures, extensive computations are performed and the results are discussed. The effects of the closures on the rural areas is also investigated. Finally, the paper determines which hospitals are most likely among those to be closed assuming that up to 10% of the existing hospitals in each of the four states were to be shut down. The overall conclusion of the empirical findings is that while differences exist among the states, efficiency, coverage, and equality measures for geographical access do not suffer significantly if only a few hospitals are closed in each state, provided these closures are done optimally to minimize impact. Further, for efficiency objectives, decision makers can follow a sequential strategy for closures and still be guaranteed optimality. The paper also discusses the effects of hospital closures on equity and it examines whether or not rural areas are disproportionately affected by closures.
Keywords: 330; Health care; Access to health care; Proximity; Hospital closures; Location problems; Facility planning